Knocking Down of Isoprene Emission Modifies the Lipid Matrix of Thylakoid Membranes and Influences the Chloroplast Ultrastructure in Poplar. Issue 3 (14th May 2015) - Velikova, Violeta; Müller, Constanze; Ghirardo, Andrea; Rock, Theresa Maria; Aichler, Michaela; Walch, Axel; Schmitt-Kopplin, Philippe; Schnitzler, Jörg-Peter
Abstract : Isoprene emission in plants is correlated with structural organization and function of plastidic membranes. Abstract: Isoprene is a small lipophilic molecule with important functions in plant protection against abiotic stresses. Here, we studied the lipid composition of thylakoid membranes and chloroplast ultrastructure in isoprene-emitting (IE ) and nonisoprene-emitting (NE ) poplar ( Populus × canescens ). We demonstrated that the total amount of monogalactosyldiacylglycerols, digalactosyldiacylglycerols, phospholipids, and fatty acids is reduced in chloroplasts when isoprene biosynthesis is blocked. A significantly lower amount of unsaturated fatty acids, particularly linolenic acid in NE chloroplasts, was associated with the reduced fluidity of thylakoid membranes, which in turn negatively affects photosystem II photochemical efficiency. The low photosystem II photochemical efficiency in NE plants was negatively correlated with nonphotochemical quenching and the energy-dependent component of nonphotochemical quenching. Transmission electron microscopy revealed alterations in the chloroplast ultrastructure in NE compared with IE plants. NE chloroplasts were more rounded and contained fewer grana stacks and longer stroma thylakoids, more plastoglobules, and larger associative zones between chloroplasts and mitochondria. These results strongly support the idea that in IE species, the function of this molecule is closely associated with the structural organization and functioning of plastidic membranes.